Pre-acceleration in the Electron Foreshock. II. Oblique Whistler Waves - Paul J. Morris; Artem Bohdan; Martin S. Weidl; Michelle Tsirou; Karol Fulat; Martin Pohl (The Astrophysical Journal, 2023)
Thermal electrons have gyroradii many orders of magnitude smaller than the finite width of a shock, thus need to be pre-accelerated before they can cross it and be accelerated by diffusive shock acceleration. One region where pre-acceleration may occur is the inner foreshock, which upstream electrons must pass through before any potential downstream crossing. In this paper, we perform a large-scale particle-in-cell simulation that generates a single shock with parameters motivated from supernova remnants. Within the foreshock, reflected electrons excite the oblique whistler instability and produce electromagnetic whistler waves, which comove with the upstream flow and as nonlinear structures eventually reach radii of up to 5 ion-gyroradii. We show that the inner electromagnetic configuration of the whistlers evolves into complex nonlinear structures bound by a strong magnetic field around four times the upstream value. Although these nonlinear structures do not in general interact with cospatial upstream electrons, they resonate with electrons that have been reflected at the shock. We show that they can scatter, or even trap, reflected electrons, confining around 0.8% of the total upstream electron population to the region close to the shock where they can undergo substantial pre-acceleration. This acceleration process is similar to, yet approximately three times more efficient than, stochastic shock drift acceleration.